Feeding and greening the world : - Tribe, D. E. (Cab international, 1994)
This book provides a dispassionate analysis of the state of these problems in the world. Avoiding hyperbole and without minimising the dangers, it explains why the future should be faced with confidence. Progress in managing the world’s natural resources in ways that are sustainable - environmentally, economically, socially and nutritionally - is too slow because knowledge is too limited. The increased knowledge that is urgently needed can only come from the global network of agricultural research. Yet governments in both the North and South are starving research of the resources that it must have. Unless present policies are changed, the international research network - mankind’s lifeline to the future - will be rendered ineffective. The author argues his case in a jargon-free way that will appeal to a wide range of readers concerned with the future of humankind